Peningkatan Implementasi Sistem Manajemen Mutu ISO 9001:2015 pada Industri Air Minum dalam Kemasan PT Makmur Bersama Sahabat - Raimon, Raimon; Edwar, Fatmir; Effendi, Effendi; Oktrison, Oktrison; Subriadi, Fejri (Jurnal Pengabdian Cendikia Nusantara, 2025)
The need for practical drinking water has become an alternative choice for every human being. Practical drinking water is currently packaged with plactic materials that  comply with applicable standards and are known as Packaged drinking water (Air Minum Dalam Kemasan/AMDK). Companies that produce AMDK must comply with applicable standards, such as mineral water standards (SNI.3553:2015) and quality management syatem standards (ISO.001:2015). One of the AMDK companies in Padang city, namely PT Makmur Bersama Sahabat (PT.MBS). Based on the data above, the PKM ATI Polytechnic Padang team chose PT.MBS as a partner in the activity PKM at 2024. The main objective of the PKM activity is to share science and technology (IPTEK) with PT.MBS employees. Base on the results of the pre-test and post-test, information was obtained that in general the level of understanding and implementation of the ISO.9001:2015  quality management system was in the ‘Very Good” and “Good” categories. This was proven during the discussion, PKM participants asked realistic questions in accordance with the problems they face everi day in their work situations.